Study service: A tool of innovation in higher education - Monal, Isabel (UNESCO, 1984)
Case studies of study service activities (activities that adapt higher education more closely to the community) are examined. The document describes 21 such studies--one from each of 21 countries, including Guyana--undertaken by college students in the community. Background information is included on the origin, conditions, and need for study service in higher education, along with principles underlying the programmes and concept of study service. Trends are also described concerning the development and refinement of objectives, the growth and expanded role of study service programmes, the diversity of programmes, and new forms of international cooperation. After identifying problem areas regarding study service, future prospects are suggested. It is claimed that study service programmes have neglected some areas of action by focusing mainly on socio-economic objectives (rural development, and public health and hygiene), and educational objectives (elimination of illiteracy and post-elementary activities). It is recommended that attention should be directed toward broader social and cultural problems
Keywords: Study service